Ritual, Folk Competitions, Mining and Stigmatization as “Poor” in Indigenous Northern Peru: A Perspective from Contemporary Quechua-Speaking Cañarenses* - Rivera Andía, Juan Javier (Revista De Ciencia Politica, 2017)
I explore the terms in which Cañarenses consider their unequal relationships with the world that surrounds them in the context of a transnational mining project on their lands. Both the mining industry and the Peruvian State have labeled this community as ‘poor’. Based on my own fieldwork conducted between 2008 and 2011, I examine public performances of religious and cultural rituals in order to unpack the terms in which these relationships are constructed. How is fear of (and desire for) the mining project expressed? The meanings attributed to participation in (or avoidance of) these performances by the Cañarenses constitute a conceptual framework in which the label of “poverty” is being confronted. In doing so, I suggest that these Cañarenses’ rituals are particularly concerned with the image of poverty used by Peruvian society to depict them. The invisibility of the Cañarenses is, in fact, what allows and even reinforces this depiction as “poor.” Finally, I show that fear of the label of poverty is combined with criticism of the term itself, as used by the Peruvian State to describe the indigenous groups in its territory. How do the ritual performers define poverty? In which terms do they classify different degrees of poverty? What manifestations of poverty do they find relevant or significant?
Created from Fastlane, Scopus look-up
Keywords: Andes; Extractivism; Indigenous peoples; Mining; Peru